2020
DOI: 10.1103/physrevb.102.184304
|View full text |Cite|
|
Sign up to set email alerts
|

Ballistic-to-diffusive transition in spin chains with broken integrability

Abstract: We study the ballistic-to-diffusive transition induced by the weak breaking of integrability in a boundarydriven XXZ spin chain. Studying the evolution of the spin current density J s as a function of the system size L, we show that, accounting for boundary effects, the transition has a nontrivial universal behavior close to the XX limit. It is controlled by the scattering length L * ∝ V −2 , where V is the strength of the integrability-breaking term. In the XXZ model, the interplay of interactions controls th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 78 publications
(115 reference statements)
0
14
0
Order By: Relevance
“…This situation is described by the Lindblad operator [36,[49][50][51]54,60,61,64,65,[68][69][70][71][72][73][74][75]…”
Section: A Lindblad Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is described by the Lindblad operator [36,[49][50][51]54,60,61,64,65,[68][69][70][71][72][73][74][75]…”
Section: A Lindblad Boundary Conditionsmentioning
confidence: 99%
“…Beyond experimental interest, for which the Lindblad coupling is the proper microscopic description, on the theory side, this approach has allowed to unveil nontrivial properties of highly excited and correlated systems: Integrable structures, traditionally restrained to closed systems in the quantum realm [49][50][51][52][53][54][55][56]; the existence of ballistics spin transport [36,57,58] and anomalous diffusion [59][60][61] in the integrable XXZ model, thus allowing for the discovery of Kardar-Parisi-Zhang correlations [62,63] in the quantum realm [64][65][66][67]. Additionally, it has allowed to characterize the anomalous transport properties of disordered [68,69] and quasiperiodic [70] interacting systems, the persistence of ballistic transport in the presence of level repulsion induced by single impurities [71][72][73], and ballistic-to-diffusive transition induced by integrability breaking in finite-sized systems [74,75].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, we followed a similar recipe to the one described in Appendix A of Ref. [60]. For a set of parameters L, V , η and D:…”
Section: S3 Open Systems With Mpsmentioning
confidence: 99%
“…An extensive amount of work on high temperature transport focusing on spin-half models in one dimensional (1D) quantum systems [2][3][4][5][6][7][8][9][10][11] has shown that breaking integrability generally leads to diffusive energy transport. It has been analytically argued that integrability in clean systems typically leads to ballistic energy transport [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…We aim to address the question of how energy transport is affected by the model parameters, in particular how integrability affects transport in this model. Transport through the chain is simulated using the Lindblad Master Equation (LME) approach implemented using Matrix Product State (MPS) techniques [11,13,15,25].…”
Section: Introductionmentioning
confidence: 99%